2019
DOI: 10.36813/jplb.3.2.300-308
|View full text |Cite
|
Sign up to set email alerts
|

Konsentrasi C-organik dan substrat sedimen di perairan Pelabuhan Belawan Medan

Abstract: Penelitian ini bertujuan mengetahui konsentrasi Corganik dan substrat pada sedimen di perairan Pelabuhan Belawan, serta melihat korelasi antar keduanya. Lokasi penelitian dilakukan di DLKr dan DLKp Pelabuhan Belawan Medan dengan pengambilan sampel secara random sampling sebanyak 10 sampel. Analisis data menggunakan analisis korelasi Pearson product moment. Hasil penelitian menunjukkan konsentrasi Corganik berkisar 0,26-2,74%. Konsentrasi substrat pasir 61-99%, lumpur 1-29%, dan liat 0-18%. C-organik memiliki k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
1
3
0
4
Order By: Relevance
“…From the results of environmental quality monitoring carried out by PT Pelabuhan Indonesia (Persero) Regional 1 for water quality, it showed that there were no observed parameters that exceeded the threshold value for the guided Quality. The results of measuring the concentration of heavy metals in sediments based on the results of sediment sample tests, the highest heavy metal concentration in the waters of Belawan Harbour was Pb with values ranging from 15.50 -68.43 mg/kg, measurements were carried out at the point of the Harbour reclamation project and the mouth of the Deli River 1 [12]. The next highest heavy metal concentration was Cu with a range of 1.68 -21.49 mg/kg, measurements were made at the sea point of the Deli River and the mouth of the Deli River 1 [12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the results of environmental quality monitoring carried out by PT Pelabuhan Indonesia (Persero) Regional 1 for water quality, it showed that there were no observed parameters that exceeded the threshold value for the guided Quality. The results of measuring the concentration of heavy metals in sediments based on the results of sediment sample tests, the highest heavy metal concentration in the waters of Belawan Harbour was Pb with values ranging from 15.50 -68.43 mg/kg, measurements were carried out at the point of the Harbour reclamation project and the mouth of the Deli River 1 [12]. The next highest heavy metal concentration was Cu with a range of 1.68 -21.49 mg/kg, measurements were made at the sea point of the Deli River and the mouth of the Deli River 1 [12].…”
Section: Resultsmentioning
confidence: 99%
“…The results of measuring the concentration of heavy metals in sediments based on the results of sediment sample tests, the highest heavy metal concentration in the waters of Belawan Harbour was Pb with values ranging from 15.50 -68.43 mg/kg, measurements were carried out at the point of the Harbour reclamation project and the mouth of the Deli River 1 [12]. The next highest heavy metal concentration was Cu with a range of 1.68 -21.49 mg/kg, measurements were made at the sea point of the Deli River and the mouth of the Deli River 1 [12]. The concentration of Cd metal ranged from 0.9 -2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kandungan karbon organik total lebih tinggi pada tekstur fine sediment (lumpur + liat) dibandingkan dengan tekstur pasir karena karbon organik mudah diendapkan pada tekstur fine sediment. Hal ini terjadi karena fine sediment memiliki pori-pori yang kecil daripada tekstur pasir memiliki tekstur yang lebih besar sehingga mudah terbawa arus (Yolanda et al 2019). Berdasarkan hal diatas penelitian terkait bahan organik disedimen belum pernah dilakukan di Perairan Kawasan Pelabuhan Pangkal Balam.…”
Section: Pendahuluanunclassified
“…Rendahnya kosentrasi karbon organik total karena stasiun 3 dan 4 memiliki jenis tekstur sedimen yaitu pasir tertinggi yaitu 93,87% dan 94,89%. Sesuai dengan pernyataanYolanda et al (2019) bahwa tekstur sedimen yang semakin halus menyimpan karbon organik yang semakin tinggi dibandingkan dengan substrat kasar.Stasiun 5, stasiun 6 dan stasiun 7 terletak di lepas pantai dengan memperoleh konsentrasi karbon organik total berkisar…”
unclassified